PERDAGANGAN INDONESIA DENGAN NEGARA-NEGARA ASEAN DAN APEC - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
ABSTRAK In the near future Indonesian economy is getting more dependent on international trade with her partner in ASEAN and Asia-Pacific countries. This article attempts to compare the Indonesian benefit from AFTA and APEC as a regional economic cooperation. Under CEPT-AFTA scheme, Indonesia receive the benefit from around 50% of commodity exported, which Indonesia has export specialization, to ASEAN countries. For the next 15 years, trade resulted from CEPTAFTA scheme gives only 9.05% expansion in import value. Under the current effective protection, AFTA would not be very much of benefit to Indonesian economy. Trade with APEC, on the other hand, gives more advantages. The problem with this trade is that most of the Indonesian exports to the regionhave very low competitiveness level. In the future, Indonesian business needs to improve their competitiveness level and quick response to the market, in order to control their exports. Keywords: Indonesian exports, market